The role of HLA antigens in recurrent primary focal segmental glomerulosclerosis - Batal, Ibrahim; Khairallah, Pascale; Weins, Astrid; Andeen, Nicole K.; Stokes, Michael B. (Frontiers in Immunology, 2023)
Primary focal segmental glomerulosclerosis (FSGS), typically characterized by diffuse podocyte foot process effacement and nephrotic syndrome (diffuse podocytopathy), is generally attributed to a circulating permeability factor. Primary FSGS can recur after transplantation where it manifests as diffuse foot process effacement in the early stages, with subsequent evolution of segmental sclerotic lesions. Previous published literature has been limited by the lack of stringent selection criteria to define primary FSGS. Although immunogenetic factors play an important role in many glomerular diseases, their role in recurrent primary FSGS post-transplantation has not been systematically investigated. To address this, we retrospectively studied a multicenter cohort of 74 kidney allograft recipients with end stage kidney disease due to primary FSGS, confirmed by clinical and histologic parameters. After adjusting for race/ethnicity, there was a numeric higher frequency of HLA-A30 antigen in primary FSGS (19%) compared to each of 22,490 healthy controls (7%, adjusted OR=2.0, P=0.04) and 296 deceased kidney donors (10%, OR=2.1, P=0.03). Within the group of transplant patients with end stage kidney disease due to primary FSGS, donor HLA-A30 was associated with recurrent disease (OR=9.1, P=0.02). Multivariable time-to-event analyses revealed that recipients who self-identified as Black people had lower risk of recurrent disease, probably reflecting enrichment of these recipients with APOL1 high-risk genotypes. These findings suggest a role for recipient and donor immunogenetic makeup in recurrent primary FSGS post-transplantation. Further larger studies in well-defined cohorts of primary FSGS that include high-resolution HLA typing and genome-wide association are necessary to refine these hereditary signals.